ARTIFICIAL INTELLIGENCE IN BUILDING CONDITION MONITORING FOR MAINTENANCE AND RESILIENCE ENHANCEMENT: A BIBLIOMETRIC REVIEW OF THE LAST DECADE - Meisy Ariani; Ahmad Zaki; Guntur Nugroho (LPPM Universitas Negeri Jakarta, 2026)
In past years, a variety of methods for monitoring the condition of concrete structures have been researched and widely used, including the application of artificial intelligence (AI). AI is increasingly popular in building monitoring and has shown excellent progress over time. This article provides a detailed bibliometric and scientometric overview of “Artificial Intelligence in Building Condition Monitoring” using data from Scopus over the last decade (2014–2024), supported by VOS Viewer software. This analysis found 222 relevant documents, which were mostly journal articles, with the most publications appearing in 2022. America and China are the countries that contribute the most to this field of research. The visualization results reveal five clusters related to AI applications in building condition monitoring, with the main topics being “condition monitoring” and “machine learning.” Research trends show an increasing focus on integrating AI with other advanced technologies to improve monitoring systems and apply these innovations in various types of buildings.